The Caenorhabditis elegans INX‐4/Innexin is required for the fine‐tuning of temperature orientation in thermotaxis behavior. (31st January 2020) - Tsukamoto, Satomi; Emmei, Taishi; Nakano, Shunji; Nishio, Nana; Sasakura, Hiroyuki; Mori, Ikue
Abstract: Innexins in invertebrates are considered to play roles similar to those of connexins and pannexins in vertebrates. However, it remains poorly understood how innexins function in biological phenomena including their function in the nervous systems. Here, we identified inx‐4, a member of the innexin family in C. elegans, by a forward screening of thermotaxis‐defective mutants. The inx‐4 mutants exhibited abnormal migration to a temperature slightly higher than the cultivation temperature, called mild thermophilic behavior. Rescue experiments revealed that INX‐4 acts in the major thermosensory neuron AFD to regulate thermotaxis behavior. INX‐4::GFP fusion protein localized exclusively along axons in AFD neurons. In addition, over‐expression of INX‐4 in AFD neurons induced a cryophilic behavior, which is opposite to inx-4 mutants. Our findings suggest that INX‐4/Innexin in AFD may fine‐tune the execution of thermotaxis behavior when moving to desired temperatures. Abstract : Innexins in invertebrates are considered to play roles similar to those of connexins and pannexins in vertebrates. Here, we identified inx‐4, a member of the innexin family in C. elegans, by a forward screening of thermotaxis‐defective mutants. Our findings suggest that inx‐4 /Innexin may fine‐tune the execution of thermotaxis behavior when moving to desired temperatures.